Sofrimento, prazer e estratégias de enfrentamento de atendentes de recepção em Hospital Militar: estudo exploratório clínico - Ferreira, Marco Antonio Diogo (2018)
The present study aims to characterize the relationships of pleasure and suffering in the work of the reception attendants of specialized ambulatory clinics, of the Hospital of the armed forces of Brasilia/DF, to identify the strategies of confrontation developed by the reception attendants through the experiential reality of their work activity and understand the significance that they attribute to their professional action. Mobilized by living conflict problem, finds the attendant in front of conflicts between the institutional regulation, the expectation of the users of the health systems served in the military hospital and their own action. Is used in this study of the potentialities of the psychoanalytic clinical referential that involve the clinical investigative possibility, the signalling of a therapeutic proposition and the use of the psychoanalytic theory itself as theoretical reference for Approach of the phenomenal field of studies. It was sought to categorize the psychic dimensions of research, through propositions of the field of the psychopathology of work, according to the psychoanalytic perspective proposed by Christophè Dejours. The methodology develops through clinical interviews, analysis of the speech through the establishment of units of direction, from the cut of the speech of the attendants, the specification of these units of meaning in categories and subcategories, According to the theoretical reference used, in representation to the dimensions of pleasure, suffering and strategies of coping proposals, as well as the clinical analysis of the psychic dynamics of what is shown in the speech of the attendants. It is also proposed to establish the correlation between clinical posture and theoretical approach, phenomenological expressiveness and language, in human intersubjective relations. This study is proposed to reinsert the human being in the field of Psicopathology, as a science that studies the fundamental affective disposition of the psychic being, which must be understood within human bases and from the human, presenting it as an elaborate agent of its own history and its meaning. It mobilizes emotion, feeling, thought, reflection and action, in the effort of expliciting in the affective dynamics involved in the reality of the work of these professionals, to whom it is sought to give opportunity of own meaning through the word.